Implementation of Rewarding Strategies in the Form of Incentives at PT. Indonesian Earthworks - Anton Budi Santoso; Abdul Rohman (Budapest International Research and Critics University, 2022)
This final project aims to determine the application of a reward strategy in the form of incentives to increase employee motivation at PT. Indonesian Earthworks. Rewards are incentives or motivations to develop the performance achieved by individuals, usually in the form of financial, namely the provision of incentives, allowances, bonuses, and commissions. The study concluded that providing rewards in the form of incentives under the work performance that has been sacrificed could make every employee work well. In other words, there is motivation to work harder, and it will increase profits for the company. The author suggests that companies apply a strategy of giving rewards in the form of incentives to increase employee motivation and personal development (personal growth) to achieve the company's targets.